Sensitive determination of 4-O-methylhonokiol in rabbit plasma by high performance liquid chromatography and application to its pharmacokinetic investigation - Ming-Yue Li; Yu-Hai Tang; Xia Liu; Hai-Yan Lü; Xi-Yan Shi (Elsevier, 2011)
A novel high Performance liquid Chromatographie method was developed for the determination of 4-O-methylhonokiol in rabbit plasma and was applied to its pharmacokinetic investigation. Plasma samples were treated by one-fold volume of methanol and acetonitrile to remove the interference proteins. A reverse phase column of SHIM-PACK VP-ODS (150Â mmÂ ÃÂ 4.6Â mm, 5.0Â Mm) was used to separate 4-O-methylhonokiol in the plasma samples. The detection limit of 4-O-methylhonokiol was 0.2Â Î¼g/L and the linear rÃ¤nge was 0.012 â 1.536Â Î¼g/L. The good extraction recoveries were obtained for the spiked samples (84.7%, 89.3% and 87.7% for low, middle and high concentrations of added Standards, respectively). The relative standard deviation of intra-day and inter-day precisions was in the rÃ¤nge from 0.6% to 13.5%. The pharmacokinetic study of 4-O-methylhonokiol was made and the results from the plasma-concentration curve of 4-O-methylhonokiol showed a two-apartment open model. This work developed a sensitive, stable and rapid HPLC method for the determination of 4-O-methylhonokiol and the developed method has been successfully applied to a pharmacokinetic study of 4-O-methylhonokiol. Keywords: 4-O-methylhonokiol, Cortex Magnoliae Officinalis, high Performance liquid chromatography, pharmacokinetic